An interactive projector camera system on iOS (iPhone) system - Lin, Sujin. (2012)
The aim of this project is to design a new interactive application for a mobile Projector-Camera System. The mobile system was later designed to interact with a background Projector-Camera System.In the mobile Projector-Camera System, it involves the use of a pico-projector and a smart phone that comes with in-built camera, whereas a background Projector-Camera System uses a PC, a web camera, and a projector. A Projector-Camera technique used for calibration will also be explained in this report.The main interaction method between the mobile and background systems is done through visual communication. By giving visual cues to the background system, the mobile system is able to give the background system certain instructions.A simple game similar to the traditional brick game "Tetris" is being designed for the application to demonstrate such interaction. The mobile Projector-Camera System will act as a controller in response to the traditional gaming console machine, providing the user a way to play the game much more interactively.